Gambaran Pertumbuhan Dan Perkembangan Anak Usia Prasekolah - Aprilia, Bunga; Indriati, Ganis; Fitri, Aminatul (Universitas Pahlawan Tuanku Tambusai, 2024)
The preschool period is an important phase that greatly influences the formation of a child's foundational abilities in various aspects, such as physical, mental, social, and emotional, which will ultimately affect their growth and development. This study aims to understand the growth and development of preschool children so that early interventions can be implemented. This research is a quantitative study with a cross-sectional approach. The sample size in this study is 170 children from Kindergarten AN Namiroh 3th and Pembina 2nd in the Tuah Madani. The sample in this study was taken using proportionate random sampling. Data collection on growth used anthropometry, and developmental used the Developmental Pre-Screening Questionnaire. The analysis used is descriptive. The research findings that 3 respondents (1.8%) fall into the underweight, 107 respondents (62.9%) into the normal, 46 respondents (27.1%) into the overweight, and 14 respondents (8.2%) into the obesity. The developmental screening results show that 138 respondents (81.2%) are in the appropriate development, 23 respondents (13.5%) in the questionable development, and 9 respondents (5.3%) in the deviating development. Preschool children have mostly normal growth and developmental aspects appropriate for their age. Parents and educators need to provide proper nutrition and appropriate stimulation to support the growth and development of preschool children optimally.